STRATEGI PENGELOLAAN KAWASAN MANGROVE DI KECAMATAN LEMBAR KABUPATEN LOMBOK BARAT - Diah Permata Sari; Muhamad Husni Idris; Hairil Anwar; Kornelia Webliana B (JURNAL HUTAN PULAU-PULAU KECIL, 2022)
Mangrove area management that does not pay attention to environmental impacts will lead to degradation vulnerability of habitat and mangrove species. This research was conducted using observation and interview methods. Interviews were conducted by purposive sampling using key informants. Data were analyzed using SWOT to identify management strategies for mangrove areas in Lembar District. The results showed that the management strategy of mangrove areas in Lembar District was in quadrant I or an aggressive strategy. Priority strategies in managing mangrove areas in Lembar District include: (a) Formulate regulations on the conservation and utilization of mangrove areas by involving all community groups, (b) Develop a mangrove data bank in collaboration with academics through education, research and service, (c) Prepare zoning plans for the utilization of the Teluk Lembar coastal area, especially mangrove areas to prevent conflicts over utilization , (d) Develop an ecotourism development plan by considering the carrying capacity, and (e) Implementation of enrichment planting programs and widening of mangrove green lanes to increase the effectiveness of the role of mangroves as bioremediators.